Decentralization, Fiscal Effort and Social Progress in Colombia at the Municipal Level, 1994-2009: Why Does National Politics Matter? (2016)
The chapter explores the relationship between political competition and effective public goods delivery systems in a decentralized context to study whether the awareness generated through such a competitive environment and the existence of more political options are a part of the causal mechanisms for effective governance. In particular, we want to observe the effect of electoral competition on the incentives to build fiscal capacity and provide public goods, such as education and water, that are, to a large extent, the responsibility of the local municipalities. The research hypothesis is that political competition strengthens the decentralized municipalities through building their local fiscal capacity. In turn, the fiscal capacity is the fundamental variable that explains the differences in sector performance across local governments. Local fiscal capacity brings about better policy outcomes, as well as a better match between resources and the needs—what we call responsiveness—which simultaneously ensures greater efficiency in local spending. Using a rich panel municipal data set from 1994 to 2009, we have shown that on comparing the differences across education and the water and sewerage sectors, the power of fiscal effort appears to be the driving force behind better policy outcomes than any other resource commonly made available to the municipalities, such as national transfers or royalties.